On the strength of joints of metal-plastic composites of hot-formed steel with an AlSi coating and a thermosetting fiber reinforced compression material. (April 2021) - Wehler, S; Moritz, P; Fischer, F; Gude, M
Novel manufacturing techniques and application of new hybrid materials in the automotive industry increase the challenges in adhesive bonding. One of these is the bonding of coated materials such as high-strength steel with an aluminum-silicon (AlSi) coating, which is mostly used in safety-relevant components such as the front or side bumpers. To further improve the mechanical properties, these steel structures can be locally reinforced with a fiber-reinforced compression molding compound (SMC). In this process, the SMC is pressed directly onto the structure, without any pre-treatment of the surface of the steel, whereby the thermosetting resin matrix forms an adhesive bond with the AlSi coating. The choice of a suitable base resin system is of decisive importance for the joint strength of such directly joined hybrid composites and thus also for the overall performance. Therefore three SMC formulations with different base resins were tested for direct adhesion to a metallic surface of a hot-formed steel with an AlSi coating. The aim of this investigation is to identify a correlation between energetic as well as optical surface characteristics and the mechanical strength of such direct hybrid joints. Furthermore, it shall be examined whether a modification of the base resin in the polymer has a significant influence on the bonding strength and the fracture pattern. For this, the project focuses on new methods for the mechanical testing of metal-plastic hybrid composites.